Synthesis and biological activity of new 2-amino-4-[3-methyl-3-(5,6,7,8-tetrahydro-2-naphthyl)cyclobuty]thiazole derivatives - Koparir, M; Cansiz, A; Ahmedzade, M (Pleiades Publishing Ltd, 2004)
2-Amino-4-[3-methyl-3-(5,6,7,8-tetrahydro-2-naphthyl)cyclobutyl]thiazole was synthesized by reaction of 1-methyl-1-(5,6,7,8-tetrahydro-2-naphthyl)-3-chloroacetylcyclobutane with thiourea in ethanol, and its subsequent transformations afforded new derivatives which were tested in vitro for antibacterial activity against some bacteria using the disk diffusion technique.